Return to run after partial amputation of the ankle: clinical assessment and instrumental evaluation - Pedrazzini, Alessio; Ceccarelli, Francesco; Martelli, Alessandra; Marenghi, Letizia; Petraglia, Federica; Romiti, Davide; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2014)
Background and aim of the work: the traumatic amputation or partial amputation of a portion of the lower limb is one of the most serious and not so rare road accident and job injury. There are few cases reported of replantation of the lower extremities rather than amputation surgery. This work describes a case of partial amputation of the right ankle. Methods: the emergency treatment consisted of rigorous lavage and debridement, reduction, stabilization of the ankle and restoreation of the neurovascular and soft tissues lesions. Because of cutaneous necrosis another surgical treatment of reverse rotation flap was needed. The good outcome has been documented with foot pressure analysis, stabilometric evaluation and gait and jump analysis based on measurements of acceleration. Results: after seven months of personalized rehabilitation program the patient walks without devices, has recovered functional of range of movement and had no neurological deficit or subjective problems. Currently the subject has returned to his job and runs without pain. Conclusions: emergency foot salvage treatment was possible thanks to a close collaboration among different physicians with specialized skills, good emergency management and an adequate infrastructure.